Oxidant-antioxidant levels in patients with bladder tumours. (9th April 2021) - Günes, Mustafa; Eryilmaz, Recep; Aslan, Rahmi; Taken, Kerem; Demir, Halit; Demir, Canan
Abstract: Purpose: We have aimed to determine whether oxidants-antioxidants play a role in the etiopathogenesis of bladder tumour by measuring their levels in the serums of patients with bladder tumour. Material method: Thirty patients with bladder tumour with superficial bladder tumour and 27 normal healthy volunteers were included in the study. Four cc of venous blood was taken from these patients and volunteers in the control group and centrifuged at 5000 rpm for 10 minutes and divided into serum and plasma. The activities of xanthine oxidase, glutathione reductase, glutathione-s transferase, reduced glutathione and superoxide dismutase enzymes in serum were then measured spectrophotometrically. Findings: Antioxidant parameters (glutathione-s-transferase, reduced glutathione, superoxide dismutase and glutathione reductase) in the serum of patients with bladder tumours were found statistically significantly lower than control group ( p < .05). On the other hand, xanthine oxidase which is an oxidant indicator, was found significantly higher in patients with bladder cancer than control group ( p < .05). Conclusion: Oxidative stress is effective in the etiopathogenesis of bladder tumour. We, therefore, believe that antioxidants are protective against bladder tumours and will be effective in the treatment of bladder tumours.